2015
DOI: 10.1002/xrs.2583
|View full text |Cite
|
Sign up to set email alerts
|

Choice of X‐ray mass attenuation coefficients for PIXE analysis of silicate minerals and rocks

Abstract: The accuracy of each of three mass attenuation coefficient databases was assessed using particle-induced X-ray emission measurements performed on well-characterized, homogeneous silicate glass and mineral standards. In a fundamental parameters computation, the absolute efficiency constants of the light elements Mg, Al and Si, found within each standard, were determined. These were compared with the efficiency constants deduced from separate particle-induced X-ray emission measurements performed on pure targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Equation (5) suggests that tomograms acquired at two different X-ray energies can be used to calculate the spatial distributions of electron density and effective atomic number. This is the basis of the DECT technique, which has been in use for almost 30 years (Haghighi et al, 2011;Landry et al, 2011;Siddiqui & Khamees, 2004;Wellington & Vinegar, 1987), but improving inversion methods is still an active research field (Alves et al, 2015(Alves et al, , 2014Heirwegh et al, 2015;Jussiani & Appoloni, 2015) for applying DECT as a quantitative probe of complex materials.…”
Section: Dual-energy Computed Tomographymentioning
confidence: 99%
“…Equation (5) suggests that tomograms acquired at two different X-ray energies can be used to calculate the spatial distributions of electron density and effective atomic number. This is the basis of the DECT technique, which has been in use for almost 30 years (Haghighi et al, 2011;Landry et al, 2011;Siddiqui & Khamees, 2004;Wellington & Vinegar, 1987), but improving inversion methods is still an active research field (Alves et al, 2015(Alves et al, , 2014Heirwegh et al, 2015;Jussiani & Appoloni, 2015) for applying DECT as a quantitative probe of complex materials.…”
Section: Dual-energy Computed Tomographymentioning
confidence: 99%
“…Comparison of PAMPA results for quantification of synthetic and mineral, thin and bulk samples, to results from GUPIX was encouraging, and the authors consider PAMPA an alternative quantification tool to GUPIX for PIXE. Heirwegh et al (2015) assessed the accuracy of three different mass attenuation coefficient databases (XCOM, FFAST and a 'mixed' database) for PIXE analysis using wellcharacterised, homogeneous silicate glass and mineral reference materials and found that average efficiency constant discrepancies were reduced by adopting the 'mixed' database. The same authors also assessed the accuracy of PIXE for analysis of major and minor elements in silicate glasses and minerals using the new GUPIX MAC database (Heirwegh et al 2016).…”
Section: Software and Iba Data Evaluationmentioning
confidence: 99%
“…These differed by ~7% from the values predicted by the GUYLS utility in the current GUPIX package that employs XCOM MACs. Subsequently, the same method was applied to a suite of well‐characterized silicate minerals and glasses, with the same outcome . In both works, the differences were significantly reduced by replacing XCOM MACs with FFAST values for the following specific cases that pertain to K X‐rays only.…”
Section: Attenuation Coefficient Schemesmentioning
confidence: 99%
“…In the second panel, this discrepancy is resolved though the MIXED database. The difference in chemical environment between each of the two elements aluminum and silicon and the corresponding oxides causes a small difference (1–1.5%) in K‐shell fluorescence yields . The oxide H ‐values in all three scenarios were therefore adjusted to their single‐element equivalents, with the aim of having a single‐element H ‐curve.…”
Section: K X‐raysmentioning
confidence: 99%
See 1 more Smart Citation